Increased Prevalence of Celiac Disease in Girls with Turner Syndrome Detected Using Antibodies to Endomysium and Tissue Transglutaminase - PM Gillett; HR Gillett; DM Israel; DL Metzger; L Stewart; J-P Chanoine; HJ Freeman (Canadian Journal of Gastroenterology)
OBJECTIVE: To establish the prevalence of celiac disease (CD) in girls with Turner syndrome (TS) in British Columbia.